Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In reducing the sum $S_n = \sum_{1\leq j<k\leq n}(\frac{1}{k-j})$ to a closed form, the authors start by replacing $k$ with $k+j$, such that $S_n = \sum_{1\leq j<k+j\leq n}(\frac{1}{k})$. The next step then reduces $S_n$ to $\sum_{1\leq k\leq n}\sum_{1\leq j\leq n-k}(\frac{1}{k})$, and giving "summing first on j" as an explanation.

I understand how $[1\leq j < k \leq n]=[1\leq k\leq n][1\leq j < k]=[1\leq j \leq k][j<k\leq n]$ (where $[P]$ denotes the Iverson bracket), which is used in reducing many other sums in the book. But how do the authors use this identity to reduce $\sum_{1\leq j<k+j\leq n}(\frac{1}{k})$ to $\sum_{1\leq k\leq n}\sum_{1\leq j\leq n-k}(\frac{1}{k})$? Is there any other identity used, or the previous one is somehow maniuplated?

share|cite|improve this question
I think the last part of your Iversonian equation should be $[1 \leq j \leq n][j < k \leq n]$ – Dongie Agnir Jul 10 '15 at 1:21
up vote 3 down vote accepted

$$k+j\leqslant n\iff\begin{cases}k\leqslant n-j\leqslant n,\quad\text{since }1\leqslant j\\\\j\leqslant n-k\end{cases}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.